Technology and gender issues : S'pore junior college students' perspectives. - Lim, Rita Kwang Imm. (2008)
This research was undertaken to investigate some of the underlying causes for the under-representation of women in the field of computing and technology. It also seeks to find out the pattern of Internet use by girls in relation to boys.